El tiempo de tránsito del pulso detecta cambios en la presión arterial en respuesta a estimulación eléctrica vestibular y cambio de postura - Pliego Carrillo, Adriana Cristina; Vega, Rosario; Fernández, Daniel Enrique; Ledesma, Claudia Ivette; Soto, Enrique (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
The interaction of the vestibular organs with the cardiovascular system is a relevant research field with clinical applications that contribute to the understanding of cardiovascular modulation due to movement and posture. The current noninvasive measurement of blood pressure (BP) consists of an inflatable cuff that is unsuitable to perform movement tasks. However, Pulse-Transit Time (PTT), an indirect method that estimates BP from electrocardiographic (ECG) and photoplethysmographic (PPG) recordings, may detect BP variations during dynamic experiments. Galvanic vestibular stimulation (GVS) is considered an analog to mechanical stimulation. Research with GVS has been done involving static and dynamic tasks. Our study aims to determine if PTT is a suitable method to be included in GVS experiments to detect BP modulation. PTT was calculated from 16 healthy subjects during GVS; stimulation was applied while seated and standing. PTT increased during the stimulation period in both positions. The increase was statistically significant only for subjects standing. These findings are following previous GVS studies that monitor BP invasively in animal models. As we expected, an increase in PTT during GVS was observed. Additionally, the increase was slightly different for subjects seated and standing. Overall, results indicate that PTT is an effective method to estimate transient BP changes during GVS.